The influence of human capital on job creation by SMEs in South Africa - Meletse, Dieketseng Tsepuoe (My University, 2019)
Background: There is a significant body of research supporting a narrative that small and medium sized enterprises (SMEs) play a key role in promoting economic development and enhancing job creation. However, SMEs are also characterised by high failure rates. Given their potential to create jobs, SMEs in South Africa do not yield the much needed jobs despite government programmes to enhance SME job creation. The importance of determining which entrepreneuship capital elements foster SME success the most cannot be overemphasised; human capital being the focus of this study. Aim: Human capital is broad, and this study aims to determine which of its elements influence job creation the most. The study therefore contributes to existing research by assisting government to prioritise limited resources to areas which will yield job creation the most in the SME cluster. Setting: The scope of this research is limited to entrepreneurs who own SMEs that employ fewer than 201 employees and are based in South Africa. The sample is across all stages of entrepreneurship. Methods: The study used secondary data of a survey which was initially conducted for another study. In an attempt to determine the influence of different human capital elements on SME job creation, a correlation and logistical regression analysis were conducted on various elements of human capital. Results: The findings suggest that general human capital influences SME job creation the most. Additionally, no statistically significant evidence was found to suggest that entrepreneurship specific human capital influences SME job creation. Conclusion: The study concludes that general human capital (formal general education and work experience) are preconditions of SMEs’ ability to create jobs and serves as a basic building block of entrepreneur trainability on other forms of human capital.
MBA
Keywords: Small business -- South Africa. Human capital. Labor economics.